2021
DOI: 10.3390/nano11112927
|View full text |Cite
|
Sign up to set email alerts
|

Distance-Dependent Fluorescence Resonance Energy Transfer Enhancement on Nanoporous Gold

Abstract: Fluorescence resonance energy transfers (FRET) between cyan fluorescent protein (CFP) and yellow fluorescent protein (YFP) on nanoporous gold (NPG) are systematically investigated by controlling the distance between NPG and fluorescent proteins with polyelectrolyte multilayers. The FRET between CFP and YFP is significantly enhanced by NPG, and the maximum enhancement is related to both ligament size of NPG and the distance between NPG and proteins. With the optimized distance, 18-fold FRET enhancement was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It is shown that the efficiency of energy transfer can be both increased and decreased and depends on the properties of the plasmon resonance of metal NPs, the mutual arrangement of the system components and the distance between the donor-acceptor pair and the metal NP, as well as on the spectral overlap between them [7][8][9]. In addition, the plasmon effect makes it possible to significantly increase the distances at which energy transfer occurs, as was shown in the articles [10][11][12].…”
Section: Introductionmentioning
confidence: 94%
“…It is shown that the efficiency of energy transfer can be both increased and decreased and depends on the properties of the plasmon resonance of metal NPs, the mutual arrangement of the system components and the distance between the donor-acceptor pair and the metal NP, as well as on the spectral overlap between them [7][8][9]. In addition, the plasmon effect makes it possible to significantly increase the distances at which energy transfer occurs, as was shown in the articles [10][11][12].…”
Section: Introductionmentioning
confidence: 94%
“…Several studies [23,29–37] investigated the modification of the FRET efficiency using plasmonic or photonic nanostructures. For example, the works of Bidault et al ., [23] Sanz‐Paz et al [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [23,[29][30][31][32][33][34][35][36][37] investigated the modification of the FRET efficiency using plasmonic or photonic nanostructures. For example, the works of Bidault et al, [23] Sanz-Paz et al [29] and Asgar et al [30] showed that the FRET efficiency deteriorates in the presence of plasmonic nanostructures, while Torres et al, [31] Lunz et al [32] and Zambrana-Puyalto et al [33] reported on the improvement of the FRET efficiency with plasmonic structures.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue aims to provide an overview of the current advances in nanophotonic and optical nanomaterials in China and to prompt new interest in this field. The collected eight articles [1][2][3][4][5][6][7][8] highlight the latest progress in nanophotonics and materials science, including developments of novel nanomaterials and ingenious nanoscale designs. These contributions may unveil new opportunities to control light, provide effective ways to optimize targeted performances, and have important implications for novel photonic devices operating beyond the diffraction limit.…”
mentioning
confidence: 99%
“…Nanomaterials have unique mechanical, electronic, and optical properties due to the strong confinement of electrons, photons, and phonons at the nanoscale. Particularly, nanoporous gold (NPG) was used by Cui et al to investigate the enhancement of fluorescence resonance energy transfer (FRET) based on polyelectrolyte multilayers as dielectric spacers between fluorescent protein pairs and plasmonic nanostructures [1], which resulted in a significant improvement on the fluorescence intensity and FRET efficiency. In a study by Kong et al, cadmium telluride (CdTe) was assembled on an AuAg alloy substrate to obtain a fivefold enhancement in terahertz emission compared with that based on silicon substrate [2], thus providing an effective way to produce small, thin, and efficient terahertz photonic devices.…”
mentioning
confidence: 99%